2011
DOI: 10.2174/156652411797536679
|View full text |Cite
|
Sign up to set email alerts
|

Xanthones from Mangosteen Extracts as Natural Chemopreventive Agents: Potential Anticancer Drugs

Abstract: Despite decades of research, the treatment and management of malignant tumors still remain a formidable challenge for public health. New strategies for cancer treatment are being developed, and one of the most promising treatment strategies involves the application of chemopreventive agents. The search for novel and effective cancer chemopreventive agents has led to the identification of various naturally occurring compounds. Xanthones, from the pericarp, whole fruit, heartwood, and leaf of mangosteen (Garcini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(136 citation statements)
references
References 72 publications
2
130
0
4
Order By: Relevance
“…Indeed, due to its known role in carcinogenesis, angiogenesis and apoptosis, COX-2 has been proposed as a good target for the development of chemopreventive and anti-cancer drugs [103]. Our studies also revealed that Caveolin-1 reduces COX-2 expression via a -catenin/Tcf-Lef-dependent transcriptional mechanism.…”
Section: The -Catenin/tcf-lef Connectionsupporting
confidence: 59%
“…Indeed, due to its known role in carcinogenesis, angiogenesis and apoptosis, COX-2 has been proposed as a good target for the development of chemopreventive and anti-cancer drugs [103]. Our studies also revealed that Caveolin-1 reduces COX-2 expression via a -catenin/Tcf-Lef-dependent transcriptional mechanism.…”
Section: The -Catenin/tcf-lef Connectionsupporting
confidence: 59%
“…Besides polyphenols, it has been demonstrated that xanthones exhibit a potent antioxidant activity. Many of naturally occurring xanthones are found in the pericarp of G. mangostana L. [5].…”
Section: Discussionmentioning
confidence: 99%
“…The most studied xanthones are a-, b-and c-mangostins, garcinone E, mangostenones and gartanin. The antioxidant, antiinflammatory, antibacterial and antiviral activities of xanthones are described [5]. The antineoplastic activity of a-mangostin (a-M; 1,3,6-trihydroxy-7-methoxy-2,8-diprenyl-9H-xanthen-9-one), the most representative xanthone in mangosteen pericarp (78% content), has been established on human hepatoma [6], breast cancer [7] and pancreatic cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its sweet pulp with unique taste, mangosteen is also attractive due to natural phenolic compounds such as xanthones and flavonoids that mostly reside in its purple-coloured pericarp ( Figure 1). These bioactive compounds are known to have medicinal properties such as anticarcinogenic, antiinflammatory and antioxidant (Akao et al 2008;Shan et al 2011). Interestingly, the molecular mechanism of these compounds in mangosteen has not been elucidated and systems biology approach such as transcriptomics can be utilised to catalogue its gene expression.…”
Section: Introductionmentioning
confidence: 99%